The Influence of Financial Inclusion, Financial Literacy, Financial Management, and Financial Technology on MSME Performance - Ernawati, Yuniar; Rahmawati, Ika Yustina; Purwidianti, Wida; Endratno, Hermin (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research aims to examine the influence of financial inclusion, financial literacy, financial management, and financial technology on the performance of MSMEs. This research uses a quantitative approach. The sample in this research was 100 MSMEs in Banyumas Regency. Sampling using the method non probability sampling with technique purposive sampling. The data collection technique in this research uses a questionnaire. The data analysis tool used is SPSS 26. The research results show that financial inclusion has no effect on MSME performance, financial literacy has a positive effect on MSME performance, financial management has a positive effect on MSME performance, and financial technology has no effect on the performance of MSMEs.